Exosomal microRNAs and other non-coding RNAs as colorectal cancer biomarkers: a review. (30th November 2019) - Francavilla, Antonio; Turoczi, Szimonetta; Tarallo, Sonia; Vodicka, Pavel; Pardini, Barbara; Naccarati, Alessio
Abstract: The circulating human transcriptome, which includes both coding and non-coding RNA (ncRNA) molecules, represents a rich source of potential biomarkers for colorectal cancer (CRC) that has only recently been explored. In particular, the release of RNA-containing extracellular vesicles (EVs), in a multitude of different in vitro cell systems and in a variety of body fluids, has attracted wide interest. The role of RNA species in EVs is still not fully understood, but their capacity to act as a form of distant communication between cells and their higher abundance in association with cancer demonstrated their relevance. In this review, we report the evidence from both in vitro and human studies on microRNAs (miRNAs) and other ncRNA profiles analysed in EVs in relation to CRC as diagnostic, prognostic and predictive markers. The studies so far highlighted that, in exosomes, the most studied category of EVs, several miRNAs are able to accurately discriminate CRC cases from controls as well as to describe the progression of the disease and its prognosis. Most of the time, the in vitro findings support the miRNA profiles detected in human exosomes. The expression profiles measured in exosomes and other EVs differ and, interestingly, there is a variability of expression also among different subsets of exosomes according to their proteic profile. On the other hand, evidence is still limited for what concerns exosome miRNAs as early diagnostic and predictive markers of treatment. Several other ncRNAs that are carried by exosomes, mostly long ncRNAs and circular RNAs, seem also to be dysregulated in CRC. Besides various technical challenges, such as the standardisation of EVs isolation methods and the optimisation of methodologies to characterise the whole spectrum of RNA molecules in exosomes, further studies are needed in order to elucidate their relevance as CRC markers.